Leptin acts on neoplastic behavior and expression levels of genes related to hypoxia, angiogenesis, and invasiveness in oral squamous cell carcinoma - Eliane Macedo Sobrinho Santos; Talita Antunes Guimarães; Hércules Otacílio Santos; Lilian Mendes Borborema Cangussu; Sabrina Ferreira de Jesus; Carlos Alberto de Carvalho Fraga; Claudio Marcelo Cardoso; Sérgio Henrique Souza Santos; Alfredo Maurício Batista de Paula; Ricardo Santiago Gomez; André Luiz Sena Guimarães; Lucyana Conceição Farias (Tumor Biology, 2017)
Leptin, one of the main hormones controlling energy homeostasis, has been associated with different cancer types. In oral cancer, its effect is not well understood. We investigated, through in vitro and in vivo assays, whether leptin can affect the neoplastic behavior of oral squamous cell carcinoma. Expression of genes possibly linked to the leptin pathway was assessed in leptin-treated oral squamous cell carcinoma cells and also in tissue samples of oral squamous cell carcinoma and oral mucosa, including leptin, leptin receptor, hypoxia-inducible factor 1-alpha, E-cadherin, matrix metalloproteinase-2, matrix metalloproteinase-9, Col1A1, Ki67, and mir-210. Leptin treatment favored higher rates of cell proliferation and migration, and reduced apoptosis. Accordingly, leptin-treated oral squamous cell carcinoma cells show decreased messenger RNA caspase-3 expression, and increased levels of E-cadherin, Col1A1, matrix metalloproteinase-2, matrix metalloproteinase-9, and mir-210. In tissue samples, hypoxia-inducible factor 1-alpha messenger RNA and protein expression of leptin and leptin receptor were high in oral squamous cell carcinoma cases. Serum leptin levels were increased in first clinical stages of the disease. In animal model, oral squamous cell carcinoma–induced mice show higher leptin receptor expression, and serum leptin level was increased in dysplasia group. Our findings suggest that leptin seems to exert an effect on oral squamous cell carcinoma cells behavior and also on molecular markers related to cell proliferation, migration, and tumor angiogenesis.